NEUROBIOLOGY RELATIONSHIP BETWEEN STUNTING AND THE RISK OF SPEECH DELAY: A NARRATIVE REVIEW - Nurussyariah Hammado; Herman Herman; Yade Kurnia Yasin; Nurul Ichsaniah; Suardi Suardi (Universitas Negeri Makassar, 2022)
Stunting is a disorder of growth and development of children due to chronic malnutrition and recurrent infections, especially in the first 1000 days of life. The negative impact of stunting on children, especially on the development of fine motor skills and cognitive abilities, including speech delays, but how stunting is related to speech delay in children has yet to be clearly understood due to restricted existing research and studies. This narrative review explains possible biomechanisms on how stunting causes speech delays in children.